Autoimmune hemolytic anemia associated with vitamin B12 deficiency and viral illness in DiGeorge syndrome. Case report and literature review. Issue 6 (10th June 2021) - Yousaf, Zohaib; Ata, Fateen; Iqbal, Phool; Muthanna, Bassam; Khan, Adeel Ahmad; Akram, Jaweria; Kartha, Anand
Abstract: Vitamin B12 plays a crucial role in cell maturation and differentiation. Its deficiency can lead to cytopenias and even hemolysis. We suggest regular monitoring and maintenance of Vit B12 levels in DiGeorge syndrome patients to prevent such triggers. Abstract : Vitamin B12 plays a crucial role in cell maturation and differentiation. Its deficiency can lead to cytopenias and even hemolysis. We suggest regular monitoring and maintenance of Vit B12 levels in DiGeorge syndrome patients to prevent such triggers.